Lifitegrast for the treatment of dry eye disease in adults. (22nd September 2017) - Donnenfeld, Eric D.; Perry, Henry D.; Nattis, Alanna S.; Rosenberg, Eric D.
ABSTRACT: Introduction : Dry eye disease (DED) is a common ocular disorder that can have a substantial burden on quality of life and daily activities. Lifitegrast ophthalmic solution 5.0% is the first medication approved in the US for the treatment of the signs and symptoms of DED. The aim of this article is to summarize the preclinical and clinical data on lifitegrast and discuss how lifitegrast may fit into the current treatment landscape for DED. Areas covered : A literature search of published preclinical and clinical data was conducted to review the chemistry, pharmacodynamics, pharmacokinetics, and clinical efficacy/safety of lifitegrast. The impact that lifitegrast may have on DED treatment practices is also discussed. Expert opinion : The introduction of lifitegrast provides a potentially important additional option for eye care professionals treating DED. In clinical trials conducted in adults with DED, lifitegrast ophthalmic solution 5.0% improved both signs and symptoms of DED. Of note, in 2 phase 3 trials, symptom improvements were observed as early as 2 weeks, which may be explained by lifitegrast's unique mechanism of action of blocking a specific signaling pathway in inflammation. Future research should include evaluation of whether lifitegrast can be used in combination with other DED treatments.